The Effectiveness of Social Participation Educational Program on the Feeling of Loneliness of Elderly People in Rural Areas of Baiza City (South of Fars Province) - Mahin Nazari; Fatemeh Jokar; Mohammad Fararooei; Mohammad Hossein Kaveh (Shiraz University of Medical Sciences, 2021)
Background: Decreasing and preventing isolation and social loneliness among the elderly are important fields for policymaking and action commitment in social health. Evidence shows that the nature and spectrum of an individual's social network including the quality and quantity of social relations and contact frequency can affect the old people's health considerably. Social participation leads to a decrease in mortality and depression and improves people's cognitive function. Since few interventions on assessment of the effect of social participation on old people's loneliness have been done, this study was conducted to determine the impact of the educational program of social participation on the feeling of loneliness. Methods: This is a quasi-experimental study based on convenience sampling method, on 239 elderly people aged ≥60 years living in rural regions of Baiza. The intervention was held for the intervention group during five weeks  through five 60-80 minute educational sessions. The data were collected by CCHS-SP and UCLA Loneliness Feeling Questionnaires before and after the intervention in the experiment  and control groups. The data were analyzed usingSPSS (version19). Results: The significance level was assumed 0.05 in statistical analysis. After one month of educational intervention program, the mean score of social participation increased in the intervention group from 6.17±3.86 to 17.98±3.84 after the intervention. The findings showed a remarkable improvement in loneliness feeling scores of the mentioned group form 62.24±.7.53 to 28.86±6.88 after the intervention (p<.001). The studied cases in the control group experienced no significant changes in the two mentioned variables. Conclusion: This study revealed a reduction in the feeling of the elderly in rural areas by predicting, improving, and modifying behaviors related to social participation and forming self-help groups in rural communities.